Globalizacja finansowa a szara strefa finansowa. Przeciwdziałanie praniu pieniędzy - Mirecka, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Stabilization in all its aspects has became the predominating process of the modern world. This process, hard for one-valued definition manifests itself as a structure of new coherence and dependences, which changes traditional borders of operations. Globalization of financial market is a new phenomenon relying on functional connection of national exchange markets, money markets and capital markets. This process evokes positive phenomena as well as negative. Among others, there are positive phenomena like the growth of capital mobility, decrease in cost of its functioning, the growth of safety of transaction and generation of new financial instrument. Among negative phenomena, it is necessary to mention alienation of financial market, which has contributed to revolt of financial speculation. The expansion of twilight zone is an inseparable part of speculation. The activity of twilight zone is related with process of money laundering and in this process more widest taking advantage of derivative instrument. The creation of forceful regulation is a leading task in the process of protecting the global financial market against money laundering. Banks have taken advantage of this process, or -lobe exact - banks take participation so, the fruition of new legal regulation within the confines of the EU market is of importance. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 264-271